State ownership and control in the Czech Republic - Evézen Kocenda; Jan Hanousek (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyze the extent of the integrated control of the state over privatized firms during the post-privatization decade (1995-2005) in the Czech Republic. During this period the integrated control potential of the state resembled a corporate pyramid. While pyramidal control was not fully utilized, the golden share in the hands of the state substantially enhanced its ability to control firms. In terms of corporate performance we show that state control resulted in declining and even negative corporate performance. Integrated state control was shown to be mostly inferior when compared with private types of ownership. State ownership positions are in striking contrast with the lack of capacity to push corporate performance in order to collect larger tax volumes. Lack of focus and inter-agency cooperation as well as the simple inefficiency of the state bureaucracy are the most likely reasons behind our findings.
Keywords: C30; D21; D29; G30; L21; 330; state ownership; control; corporate performance; privatization; Öffentliche Kapitalbeteiligung; Öffentliches Unternehmen; Privatisierung; Staatliche Einflussnahme; Unternehmensentwicklung; Tschechische Republik